CONCEPTION AND REALIZATION OF DIDACTIC MOVIES - Waldemar, LIB (Trends in education, 2009)
Properly realised didactic movie can make shorter student's time of perception at about 10 - 40%. Nowadays importance of didactic movie grows constantly, presentation of experiment executable in specialist scientific laboratories, discoveries and history of invention is possible only in movies. Movie in the form of short sequence is use more and more generally in multimedia didactic programs.
Keywords: media in education; technical didactic means; didactic movie.